(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses variants of indeclinable (in other terminology - invariable) nouns (hereinafter - NS) of foreign origin, which are found in a very significant number in the texts of Russian books translated from other languages.